Classifying insect pests from image data using deep learning - Mohsin, Md. Raiyan Bin; Ramisa, Sadia Afrin; Saad, Mohammad; Rabbani, Shahreen Husne; Tamkin, Salwa (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.